Assessment of Neem (Azadirachta indica) and Moringa (Moringa oleifera) bio-pesticides in the control of field insect pests of Okra (Abelmoschus esculentus) in Ilorin, Nigeria - Zubairu, Memunat Abike; Yusuf, I.O; Alagbe, Alagbe A.V; Babatunde, S.F; Uddin, R.O (FUDMA JOURNAL OF SCIENCES, 2025)
A field experiment evaluated the effectiveness of aqueous leaf extracts of neem and moringa against insect pests affecting okra. The study included five treatments: aqueous leaf extracts of neem, moringa, a 1:1 mixture of both, cypermethrin, and a control group. A Randomized Complete Block Design was employed, consisting of three blocks and three replicates. In total, fifteen plots were established, each containing twelve plants, using the okra variety NH47-4. The plots were treated with various extracts to assess their efficacy against field insect pests. The initial spraying took place two weeks after germination, followed by additional applications at ten-day intervals. Insects on the tag plant were sampled, counted, and recorded starting from the seedling stage (four weeks after planting) until harvest. The findings revealed that All aqueous extracts demonstrated a significant reduction in insect pest infestation on okra compared to the control group; however, the aqueous leaf extract of neem exhibited the highest efficacy among the treatments. Farmers are advised to use neem aqueous extract as an eco-friendly and affordable alternative to chemical pesticides for sustainable okra production
Keywords: Aqueous extracts; bio-pesticides; okra; pests; neem; moringa